Exploring Infant and Young Child Feeding Practices in the Royal Borough of Greenwich, London, to Improve Health and Nutrition Outcomes in Children Under 2 Years of Age - Kenyangi, Beijuka Diana; Keith, Regina Susan; Adegboye, Amanda R. Amorim (World Nutrition, 2019)
Introduction: The UK, like many other countries, is struggling to achieve two of the Global Nutrition Targets, namely increasing exclusive breastfeeding and halting the rise of childhood obesity. Identifying the infant feeding interventions that are having an impact could increase the effectiveness of cash strapped public health services in London. Improving infant feeding practices could also help halt the dangerous rise in childhood obesity.Study Aim: This study explored the Infant and Young Child Feeding (IYCF) practices and support in place to improve health and nutrition outcomes of children under 2 years of age in the Royal Borough of Greenwich, LondonMethodology: The study applied a qualitative methodology, supplemented with data on demographic characteristics of participants, collected via standardised questionnaires prior to the qualitative data collection. Categorical data are presented as absolute (n) and relative frequency (%). Qualitative data were collected using focus group discussions, semi structured interviews and key informant interviews and analysed using a thematic approach.Participants: The total sample included 35 participants: four focus groups with fifteen mothers, nine semi structured interviews, six with mothers and three fathers--all with at least one child in the target age group--and 11 key informants.Findings: Five main themes and twenty-five subthemes emerged from the qualitative data including a high level of awareness on the importance of infant feeding practices. However, only six of the key informants were aware of the borough IYCF Policy. Key informants felt that they personally would benefit from more training and resources, while more support from health workers, family and friends was very important for the other participants. Support services offered at the Children’s Centres appeared to be the most effective, in comparison to support at hospital and at home. There was a lack of cohesion among messages given at the different points of care of breastfeeding moms. Respondents reported that the Borough was implementing some aspects of its infant feeding support programmes effectively, especially through the breastfeeding support groups.Conclusions: Continuous monitoring and evaluation of current programmes and creation of sustainable links between all points of care from antenatal to postnatal period will help the Borough in achieving improved breastfeeding rates. This should improve health and nutrition outcomes for children under 2 years of age in the borough.